Open Access at the Academy of Sciences of the Czech Republic and Czech Digital Mathematical Library - Burešová, Iva; Štruncová, Jarmila (Digital Presentation and Preservation of Cultural and Scientific Heritage, 2014)
We explain the principles the Open Access Policy of the Academy ofSciences of the Czech Republic adopted as a consequence of its accession to theBerlin Declaration on Open Access. The Policy is implemented by means ofAcademy’s Institutional Repository. An example of a subject specialized open access repository is the Czech Digital Mathematics Library (DML-CZ) and theEuropean Digital Mathematics Library. We discuss a special feature of theDML-CZ represented by the highly heterogeneous collections devoted to eminent personalities of the Czech mathematics.
Keywords: Academy of Sciences of the Czech Republic; Open Access; Open Access Policy; Institutional Repository; Digital Mathematical Library; DML- CZ; collected works